A core outcome set for aphasia treatment research: The ROMA consensus statement. Issue 2 (February 2019) - Wallace, Sarah J; Worrall, Linda; Rose, Tanya; Le Dorze, Guylaine; Breitenstein, Caterina; Hilari, Katerina; Babbitt, Edna; Bose, Arpita; Brady, Marian; Cherney, Leora R.; Copland, David; Cruice, Madeline; et al.
Background: A core outcome set (COS; an agreed, minimum set of outcomes) was needed to address the heterogeneous measurement of outcomes in aphasia treatment research and to facilitate the production of transparent, meaningful, and efficient outcome data. Objective: The Research Outcome Measurement in Aphasia (ROMA) consensus statement provides evidence-based recommendations for the measurement of outcomes for adults with post-stroke aphasia within phases I–IV aphasia treatment studies. Methods: This statement was informed by a four-year program of research, which comprised investigation of stakeholder-important outcomes using consensus processes, a scoping review of aphasia outcome measurement instruments, and an international consensus meeting. This paper provides an overview of this process and presents the results and recommendations arising from the international consensus meeting. Results: Five essential outcome constructs were identified: Language, communication, patient-reported satisfaction with treatment and impact of treatment, emotional wellbeing, and quality of life. Consensus was reached for the following measurement instruments: Language: The Western Aphasia Battery Revised (WAB-R) (74% consensus); emotional wellbeing: General Health Questionnaire (GHQ)-12 (83% consensus); quality of life: Stroke and Aphasia Quality of Life Scale (SAQOL-39) (96% consensus). Consensus was unable to be reached for measures of communication (where multiple measures exist) or patient-reported satisfaction with treatment or impact of treatment (where no measures exist). Discussion: Harmonization of the ROMA COS with other core outcome initiatives in stroke rehabilitation is discussed. Ongoing research and consensus processes are outlined. Conclusion: The WAB-R, GHQ-12, and SAQOL-39 are recommended to be routinely included within phases I–IV aphasia treatment studies. This consensus statement has been endorsed by the Collaboration of Aphasia Trialists, the British Aphasiology Society, the German Society for Aphasia Research and Therapy, and the Royal College of Speech Language Therapists.